Targeting UPR branches, a potential strategy for enhancing efficacy of cancer chemotherapy. (19th October 2021) - Yu, Mengchao; Lun, Jie; Zhang, Hongwei; Wang, Lei; Zhang, Gang; Zhang, Haisheng; Fang, Jing
Abstract: Cancer cells are often exposed to cell intrinsic stresses and environmental perturbations that may lead to accumulation of unfolded and/or misfolded proteins in the lumen of endoplasmic reticulum (ER), a cellular condition known as ER stress. In response to ER stress, the cells elicit an adaptive process called unfolded protein response (UPR) to cope with the stress, supporting cellular homeostasis and survival. The ER stress sensors inositol requiring protein 1α (IRE1α), eukaryotic translation initiation factor 2 alpha kinase 3 (EIF2AK3, also called PERK), and activating transcription factor 6 (ATF6) constitute the three branches of UPR to resolve ER stress. IRE1α, PERK, and ATF6 play an important role in tumor cell growth and survival. They are also involved in chemotherapy resistance of cancers. These have generated widespread interest in targeting these UPR branches for cancer treatment. In this review, we provide an overview of the role of IRE1α, PERK, and ATF6 in cancer progression and drug resistance and we summarize the research advances in targeting these UPR branches to enhance the efficacy of chemotherapy of cancers.